Crystallographic properties of KSr2Nb5O15 - Lanfredi, S.; Cardoso, C. X.; Nobre, MAL (Elsevier B.V., 2004)
Nanostructured KSr2Nb5O15 oxide was synthesized by the polymeric precursor method, a chemical synthesis route based on the Pechini's method. The X-ray diffraction (XRD) pattern of the calcined powder at 1150 degreesC were performed in the angular range 5 less than or equal to 20 less than or equal to 120degrees with a 0.02degrees step and a fixed counting time of 30 s. The XRD data were analyzed by the Rietveld refinements using the FullProf software. The results C showed a tetragonal system with the tetragonal tungsten bronze structure (TTB) type (a = 12.4585 (2) Angstrom and c = 3.9423 (6) Angstrom, V = 611,90 (2) Angstrom). In this work, the sites occupancy by the K+ and Sr2+ cations on the TTB type structure were determined. The thermal parameters (B) were analyzed. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: KSr2Nb5O15; chemical synthesis; tetragonal tungsten bronze; Rietveld method